« L’art libérant l’architecture de la tyrannie de l’espace ». Autour de quelques textes d’Asger Jorn - Carmen Popescu (In Situ)
The following paper proposes to shed some light, from a novel angle, on the dialogue between art and architecture. It will not address the collaboration between an artist and an architect – or, if it does, only furtively; instead, it will analyse the way the first critically assesses the production of the second. By displacing the point of view, the paper considers the artistic approach from the perspective of its questioning the very principles of (modernist) architecture. Hence the choice of the topic – the writings of the Danish artist Asger Jorn – which targets directly the crisis of modernism. After a short collaboration with Le Corbusier (and Fernand Léger) for the Pavilion des Temps Nouveaux for the International Fair in Paris 1937, Jorn was to develop a steady interest for architecture, as shown by his many articles dealing with this field. His comments, as well as his disapproval of modernism, go well beyond the mere connection art/architecture and explore the way artistic creativity could change the essence of architectural conception. By doing that, Jorn does more than criticise modernism, questioning the very mechanics of modernity. The approach he builds up through his writings announces the criticality of postmodernism, while insisting on the ontology of architecture in general and, in particular, the deontology of the architect.